2008
DOI: 10.3314/jjmm.49.311
|View full text |Cite
|
Sign up to set email alerts
|

Different Genes Can Result in Different Phylogenetic Relationships in Trichophyton Species

Abstract: To determine the relationships among Trichophyton species we constructed three phylogenies, based on the nucleotide sequences of the actin, rRNA and DNA topoisomerase II genes. These phylogenies showed several conflicting branch points. For example, strains of T. verrucosum, T. concentricum and T. mentagrophytes var. erinacei were mingled with strains of Arthroderma benhamiae and could not be separated into their own phylogenic groups. In addition, strains of A. vanbreuseghemii, T. tonsurans, T. mentagrophytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Kawasaki et al [23] determines the relationships among Trichophyton species; they constructed three phylogenies based on the nucleotide sequences of the actin, rRNA, and DNA topoisomerase II genes. This study located T. concentricum in clade I, most closely related to T. mentagrophytes and Arthroderma benhamiae; therefore, the possible implication is that it is either a forerunner of the zoophilic form of T. mentagrophytes or has evolved from it.…”
Section: Causementioning
confidence: 99%
“…Kawasaki et al [23] determines the relationships among Trichophyton species; they constructed three phylogenies based on the nucleotide sequences of the actin, rRNA, and DNA topoisomerase II genes. This study located T. concentricum in clade I, most closely related to T. mentagrophytes and Arthroderma benhamiae; therefore, the possible implication is that it is either a forerunner of the zoophilic form of T. mentagrophytes or has evolved from it.…”
Section: Causementioning
confidence: 99%
“…The proposers themselves have changed the definition of T. mentagrophytes twice since it was first proposed in 1999 13−15) . Furthermore, Kawasaki et al reported a lack of stability of phylogenetic relationships from ITS sequence data alone 16) , from which the new taxonomy was concluded.…”
Section: Discussionmentioning
confidence: 99%
“…Strains without RV, ATCC, NCPF or CBS collection numbers were identified in our laboratory by morphological, physiological and molecular biological methods, including mating tests for Arthroderma species and determinations of restriction fragment length polymorphisms (RFLP)in rRNA gene ITS regions 7) . We assessed 4 genes: the 5.8S rRNA gene and ITS regions 1 and 2, a partial sequence of the actin(ACT)gene that included two introns 5) , a partial sequence of the DNA topoisomerase(TOP)2 gene that included one intron 5) and a partial sequence of the glyceraldehyde-3-phosphate dehydrogenase (GPD)gene that included one intron. The latter DNA fragment was amplified using the primers, 5-caggttgttgctgtcaacgac-3 (forward) and 5-gatgttctgggcagcggtac-3(reverse) .…”
Section: Methodsmentioning
confidence: 99%
“…The new taxa are very complicated compared with previous taxa 3) . To better understand phylogenetic relationships among Trichophyton species that are common dermatologically, we assessed 28 isolates by sequencing 3 different DNA regions not in linkage 5) . We found that each of these DNA regions yielded different phylogenies 5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation